Mesenchymal Stem Cell-Derived Microvesicles Support Ex Vivo Expansion of Cord Blood-Derived CD34+ Cells - Hui Xie; Li Sun; Liming Zhang; Teng Liu; Li Chen; Aiqi Zhao; Qian Lei; Fei Gao; Ping Zou; Qiubai Li; An-yuan Guo; Zhichao Chen; et al. (Hindawi Limited, 2016)
Mesenchymal stem cells (MSCs) are known to support the characteristic properties of hematopoietic stem and progenitor cells (HSPCs) in the bone marrow hematopoietic microenvironment. MSCs are used in coculture systems as a feeder layer for the ex vivo expansion of umbilical cord blood (CB) to increase the relatively low number of HSPCs in CB. Findings increasingly suggest that MSC-derived microvesicles (MSC-MVs) play an important role in the biological functions of their parent cells. We speculate that MSC-MVs may recapitulate the hematopoiesis-supporting effects of their parent cells. In the current study, we found MSC-MVs containing microRNAs that are involved in the regulation of hematopoiesis. We also demonstrated that MSC-MVs could improve the expansion of CB-derived mononuclear cells and CD34+ cells and generate a greater number of primitive progenitor cells in vitro. Additionally, when MSC-MVs were added to the CB-MSC coculture system, they could improve the hematopoiesis-supporting effects of MSCs. These findings highlight the role of MSC-MVs in the ex vivo expansion of CB, which may offer a promising therapeutic approach in CB transplantation.